Mobile(izing) Educational Research: Historical literacy, m-learning, and technopolitics - Smith, Bryan; Ng-A-Fook, Nicholas; Corrigan, Julie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
This research project explored the nexus between historical literacies, digital literacy and m-learning as a praxis of mobilizing technopolitics. To do this, we developed a mobile application for teacher candidates to study the absence of the Indian Residential School system as a complement to history textbooks and other curricular materials. Building on the findings of our SSHRC-funded digital history research project, we sought to engender a “technopolitics” as a form of critical historical literacy. Out of this work, we sought to understand how digital technologies contributed to recent calls to mobilize educational research and more specifically, while working to decolonize existing narratives of Canadian history beyond traditional modes of dissemination.